Motion analysis of hammer throw technique of the world top female athletes - Li, L.; Wan, B.; Guo, C.; Sun, Y. (Advances in Social Science, Education and Humanities Research, 2018)
In order to study the characteristics of the best Chinese female athlete Zheng Wang's hammer throw technique and improve her performance, we used biomechanical video analysis to analyze the technical characteristics of 6 world top female hammer players. We found that in the process of holding the ball, Zheng Wang's double stance and single stance phases in the first, third and fourth turn was reasonable, but in the second turn it was unbalanced. (2) Zheng Wang`s rotation were relatively faster, and rotation was fluent. She was one of the fastest female hammer throwers in the world. (3)During the rotation in the last turn, Zheng Wang maintained the same rotation time as the third circle, which lead to less speed-up, compare with the third circle.(4) During the rotation, the Angle of the fan was basically reasonable, but the increment of the second, third and fourth circle was unstable than that of the previous turns. (5)Through the long-term observation of Zheng Wang's training and competition, it was found that there were some problems in the psychological stability of the competition.